2009 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2009
DOI: 10.1109/iembs.2009.5333530
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated Homocysteine hormone on electrical activity in the human atrium: A simulation study

Abstract: Atrial fibrillation (AF) accounts for a large proportion of healthcare expenditure world wide. Mechanisms underlying the genesis and maintenance of AF are still poorly understood. Though AF is largely thought to be caused and perpetuated by dysfunctions of cellular ion channels, disrupted intercellular gap junctional electrical coupling, and/or structural changes in the atria, it is also associated with abnormal secretion of hormones, such as a high level of Homocysteine (Hcy). It was found that a high concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…20,21) Law, et al showed that elevated homocysteine resulted in marked changes in atrial action potentials, such as a more hyperpolarized resting potential, elevated plateau potential during the early stages of repolarization, and abbreviated action po- tential duration (APD). 22) They also found that simulated re-entrant scroll waves were sustained under high homocysteine conditions compared with self-terminated under control conditions, demonstrating the pro-arrhythmic effects of elevated homocysteine in promoting and sustain-ing AF. 22) Thus, these studies likely reflect progressive electrophysiological and structural remodeling in both atria, making sources of the arrhythmia more stable and long-lasting.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…20,21) Law, et al showed that elevated homocysteine resulted in marked changes in atrial action potentials, such as a more hyperpolarized resting potential, elevated plateau potential during the early stages of repolarization, and abbreviated action po- tential duration (APD). 22) They also found that simulated re-entrant scroll waves were sustained under high homocysteine conditions compared with self-terminated under control conditions, demonstrating the pro-arrhythmic effects of elevated homocysteine in promoting and sustain-ing AF. 22) Thus, these studies likely reflect progressive electrophysiological and structural remodeling in both atria, making sources of the arrhythmia more stable and long-lasting.…”
Section: Discussionmentioning
confidence: 94%
“…22) They also found that simulated re-entrant scroll waves were sustained under high homocysteine conditions compared with self-terminated under control conditions, demonstrating the pro-arrhythmic effects of elevated homocysteine in promoting and sustain-ing AF. 22) Thus, these studies likely reflect progressive electrophysiological and structural remodeling in both atria, making sources of the arrhythmia more stable and long-lasting. Some clinical studies have shown that aging influences the development and prognosis of patients with AF.…”
Section: Discussionmentioning
confidence: 94%
“…The effect of specific ion currents and electrolyte concentration on arrhythmogeneity was studied (Kuijpers et al, 2006; Aslanidi et al, 2008; Law et al, 2009; Varela et al, 2014; Voigt et al, 2014; Onal et al, 2017) whereas electrical remodeling, induced by AF, and its role on episodes induction is discussed by Colman et al (2013) and Lee et al (2016). Furthermore, Morgan et al (2014) reported that co-existence of structural and electrical remodeling can promote AF initiation.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies showed that hyperhomocysteinaemia is associated with procoagulant activity, 16 left atrial thrombus formation, 17 thromboembolic complications, 18 19 stroke in atrial fibrillation 19 and persistent arrhythmia after successful epicardial ablation of atrial fibrillation. 20 21 In addition, homocysteine may have arrhythmogenic effects due to changes in atrial action potentials 4 and inhibition of atrial myocyte potassium channels. 22 Therefore, a higher number of solid microemboli in our patients with hyperhomocysteinaemia might be due to a combination of arrhythmogenic and coagulopathic effects of homocysteine.…”
Section: Discussionmentioning
confidence: 99%
“… 3 The vascular effects of homocysteine are not limited to arterial atherosclerosis or venous thrombosis. 3 Hyperhomocysteinaemia also increases the risk of embolic events, 4 including embolic strokes. 5 Patients with carotid stenosis and microemboli on transcranial Doppler (TCD) have significantly higher levels of tHcy, 6 as do patients with paradoxical embolism.…”
Section: Introductionmentioning
confidence: 99%